Sub-Brand Improvement Strategy for Retail Management Study Program at XYZ University - Meilani Eka Putri Andrean; Mochammad Mukti Ali; Nunung Ayu Sofiati; Ade Salman Alfarisi; Irving Ignatius Paul Luntungan; Riyandi Nur Sumawidjaya; Anggono Raras Tirto Sakti (Dinasti Publisher, 2025)
This study aims to analyze the sub-brand strengthening of the Retail Management Study Program at XYZ University by using a SWOT analysis approach combined with the 7P marketing mix framework. The research seeks to identify the program's strengths, weaknesses, opportunities, and threats, as well as to formulate appropriate strategies within the context of higher education marketing. Based on the data analysis, the Internal Factor Analysis Summary (IFAS) score was 3.02, while the External Factor Analysis Summary (EFAS) score reached 3.25, placing the program in the aggressive (S–O) quadrant. The proposed strategies focus on leveraging internal strengths—such as a relevant curriculum, affordable tuition, digital media utilization, and adequate campus facilities—to address external opportunities including the growth of the retail industry, scholarship availability, and the program's unique positioning within the region. The final outcome presents a sub-brand development strategy based on the 7P framework, covering product, price, place, promotion, people, process, and physical evidence to strengthen competitiveness and brand identity.